+0  
 
+1
71
1
avatar+117 

Not sure how to do this one,do i convert them then divide then convert it back?

 Nov 6, 2018
 #1
avatar+94526 
+2

Remember that  a^m  x a ^n   =  a^(m + n)

 

So.....the numerator becomes

 

3^8  x 3^4   = 3^(8 +4)  =  3^12

 

And the denominator becomes

 

3^ 2  x 3^8  =  3^(2 + 8)  =  3^(10)

 

So  we have

 

3^12

_____        (1)

3^10

 

 

And

 

a^m

____    =     a^(m - n)

a^n

 

 

 

So (1)  evaluates to    3^(12- 10)   =  3^2  

 

 

 

cool cool cool

 Nov 6, 2018
edited by CPhill  Nov 6, 2018
edited by CPhill  Nov 6, 2018

21 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.